Religius Habits (Shrines) Of Svaneti - Kashia, Rusudan (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
Domestic migration from Svaneti to lowland regions took place during the 70-80s of the XX century in organized manner. It was primarily caused by the natural disasters. Svaneti people compactly settled in lowland villages don’t suspend the relations with the lands of their ancestors, shrines, first of all to the village churches: Archangel of Kvedreshi, St. Giorgi of Khopuri, Archangel of Tchvelieri. The population of Lentekhi is united by the shrine of Paki. Attending the celebration of Paki and make donations is one of the most stable traditions of Svaneti population. Retaining traditions is also revealed performing folk celebrations by Svaneti people living in different regions. Svans living in Imereti maintain the folk performance - “coming of souls” and perform it according to all the rules of the ritual. Skaroba is celebrated by voting in someone’s family. They sacrifice the cow and prey in a local way with candles. In imereti Skaroba is considered as a gatherer of a population of one village. People from Choluri have their own celebration - Khatishoba which means “worshiping the icon”.